Intrapleural administration with traditional Chinese medicine injections (Sophorae flavescentis preparations) in controlling malignant pleural effusion: a clustered systematic review and meta-analysis - Zhang, Yan; Xiao, Zheng; Liu, Hui; Cai, Da-Chun; Luo, Yao-Qin; Xu, Jiao; Luo, Feng; Huang, Jun; Jin, Yan-Yan; Fan, Teng-Yang; Zhang, Jun; Xiao, Xue; et al. (Frontiers in Pharmacology, 2025)
IntroductionSophorae flavescentis (kushen) preparations are widely used to control malignant pleural effusion (MPE) through intrapleural perfusion.ObjectivesThis analysis aims to verify the therapeutic values of perfusion with kushen preparations for controlling MPE, reveal the optimal treatment plan, suitable population, and usage, and to demonstrate their clinical effectiveness and safety.MethodsWe performed and reported this systematic review/meta-analysis (PROSPERO: CRD42023430139) following the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) guidelines. All randomized controlled trials (RCTs) concerning perfusion with kushen preparation for MPE were collected from Chinese and English databases. We clustered all eligible studies into multiple homogeneous treatment units, assessed their methodological quality using a RoB 2, pooled the data from each unit, and summarized the quality of the evidence.ResultsWe included 83 RCTs reporting three types of kushen preparation: compound kushen injection (CKI), kang’ai injection, and matrine injection. All trials were clustered into perfusion with CKI alone or with the addition of sclerosants, kang’ai, or matrine-plus platinum for controlling MPE. Compared with cisplatin alone, perfusion with CKI alone displayed a similar complete response, pleurodesis failure, and pleural progression (odds ratios =1.10, 95% CI 0.76 to 1.60; 0.80, 0.56 to 1.14; 0.63, 0.33 to 1.21). Of 14 homogeneous treatment plans, perfusion with CKI and cisplatin significantly improved the complete response (2.71, 2.30 to 3.19) and showed low pleurodesis failure (0.26, 0.22 to 0.32), pleural progression (0.22, 0.14 to 0.36), myelosuppression (0.34, 0.24 to 0.47), neutropenia (0.35, 0.26 to 0.46), gastrointestinal reaction (0.36, 0.29 to 0.44), hepatorenal toxicity (0.42, 0.28 to 0.63 and 0.32, 0.24 to 0.44), and fever (0.50, 0.30 to 0.82). These results were moderate quality (⊕⊕⊕Ο) supported by firm or conclusive information. Additionally, perfusion with kang’ai or matrine and cisplatin also improved the complete response (3.04, 1.76 to 5.26 and 1.87, 1.26 to 2.78) and displayed low pleurodesis failure (0.23, 0.14 to 0.41 and 0.27, 0.17 to 0.44). The results were moderate to low quality (⊕⊕⊕Ο to ⊕⊕ΟΟ).ConclusionCurrent moderate evidence demonstrates that CKI may be an effective palliative intervention for MPE which, combined with cisplatin, may be an optimal treatment plan. Kang’ai or matrine may be other potential choices.Systematic Review Registration:https://www.crd.york.ac.uk/PROSPERO/view/CRD42023430139